Teoria sekurytyzacji i konstruowanie bezpieczeństwa - Fijałkowski, Łukasz (Przegląd Strategiczny, 2012)
Theory of securitization is one of the most significant approaches to security in recent decades. It is used in the theoretical debate on the very nature of security and in the analysis of the security practice. The concept of securitization, associated with the so called Copenhagen School, is an attempt to conceptualize the security in a new way, without losing its analytical utility. The main object of investigation is the process of constructing the security as an intersubjective process of including/excluding the issues into/from the security sphere. Security is treated as a speech act, and the theory is aiming to gain the understanding who is securitizing, what issues are securitized, who is a referent object, why, with what results and under what conditions.